LATE CENOZOIC MAGMATISM ON THE WILHELM ARCHIPELAGO, GRAHAM COAST OF THE ANTARCTIC PENINSULA - Митрохин, О.В.; Гаврилів, Л.І.; Бахмутов, В.Г. (Institute of Geological Sciences, NAS of Ukraine, 2023)
Manifestations of the recent magmatism were discovered in the Wilhelm Archipelago near the Ukrainian research station in the West Antarctica. There are small subvolcanic dykes that intrude Paleocene granitoids on the Barchans, Forge, Booth and Dannebrog Islands. The authors studied the occurrence, petrography and geochemistry of the dyke rocks in order to find out the peculiarities of their formation. The studied dykes are typical post-plutonic fissure intrusions injected in the host granitoids after their complete consolidation and cooling. Moreover, the host granitoids were not only cooled before the dyking but they were also exhumed at the beginning of the Neogene due to of the processes of tectonic uplift and erosion. Field observation and some other features point out to the Late Neogene or Quaternary age of the dykes. Their intrusion occurred at the shallow depths. During formation, at least part of the dykes was connected with the earth’s surface. So, they were conduits for fissured volcanic eruptions. The geochemical features of the most widespread basaltic dykes call into question their genetic connection with quantitatively subordinate dykes of andesitic and dacitic composition. They probably had different sources of magma generation that were related to different geotectonic processes. Andesitic and dacitic dykes may represent the final outburst of subduction-related calc-alkaline magmatism. On the other hand, the connection between subduction processes and Late Cenozoic basaltic dyking is not obvious and requires additional research.